The University of Buenos Aires’ Programa Facultad Abierta: Reflections on a Collaborative and Political–Academic University Extension Initiative with Argentina’s Self-Managed Workers - Ruggeri, Andres; Antivero, Javier; Politi, Natalia; Vieta, Marcelo Alejandro (Alberta Journal of Educational Research, 2018)
This perspectives article offers an overview of the Programa Facultad Abierta (Open Faculty Program) written by its faculty protagonists. Through the creation and continuation of this program the authors describe the evolution of the program that emerged from the socio-political context of Argentina’s 2001-2002 economic crisis. As a university extension program associated with the University of Buenos Aires’s Faculty of Philosophy and Letters, the Programa Facultad Abierta is both socially committed and community-focused. The Programa Facultad Abierta serves as an illustrative case study of the possibilities still available to the public university for not only engaging in continuing adult education, but also for playing a key role in supporting broader proposals for social change against and beyond social exclusion and strictly capitalist prerogatives. Indeed, the experiences of the Programa Facultad Abierta shows that the public university has an important role in an academic–political project which both co-creates knowledge and collaborates with otherwise marginalized communities and working people in forging alternative socio-economic destinies together. Cet article offre un aperçu du Programa Facultad Abierta (Programme d’études libres) écrit par les acteurs clés de la faculté. Les auteurs décrivent l’évolution de ce programme, de sa création découlant du contexte sociopolitique de la crise économique de l’Argentine en 2001-2002 jusqu’à son maintien de nos jours. En tant que programme d’éducation permanente lié à la faculté de philosophie et des lettres de l’Université de Buenos Aires, le Programa Facultad Abierta est à la fois engagé socialement et axé sur la communauté. Il sert de cas d’étude pour illustrer les possibilités qu’ont encore les universités publiques de non seulement s’impliquer dans le maintien de l’éducation des adultes, mais également de jouer un rôle clé dans l’appui des propositions plus larges visant le changement social pour éliminer l’exclusion sociale et les prérogatives strictement capitalistes. Effectivement, les expériences du Programa Facultad Abierta indiquent que l’université publique a un rôle important à jouer dans un projet académique-politique qui contribue à la création des connaissances et collabore avec des communautés marginalisées et des travailleurs pour créer ensemble des destins socioéconomiques alternatifs. Mots clés : programme d’éducation permanente; université publique; mouvements sociaux; autogestion des travailleurs; Argentine